Compensatory intestinal immunoglobulin response after vancomycin treatment in humans. (1st January 2021) - Scheithauer, Torsten P. M.; Bakker, Guido J.; Winkelmeijer, Maaike; Davids, Mark; Nieuwdorp, Max; van Raalte, Daniël H.; Herrema, Hilde
ABSTRACT: Intestinal immunoglobulins (Ig) are abundantly secreted antibodies that bind bacteria and bacterial components in the gut. This binding is considered to accelerate bacterial transit time and prevent the interaction of potentially immunogenic compounds with intestinal immune cells. Ig secretion is regulated by alterations in gut microbiome composition, an event rarely mapped in an intervention setting in humans. Here, we determined the intestinal and systemic Ig response to a major intervention in gut microbiome composition. Healthy humans and humans with metabolic syndrome received oral vancomycin 500 mg four times per day for 7 days. Coinciding with a vancomycin-induced increase in Gram-negative bacteria, fecal levels of the immunogenic bacterial components lipopolysaccharide (LPS) and flagellin drastically increased. Intestinal antibodies (IgA and IgM) significantly increased, whereas peripheral antibodies (IgG, IgA, and IgM) were mostly unaffected by vancomycin treatment. Bacterial cell sorting followed by 16S rRNA sequencing revealed that the majority of Gram-negative bacteria, including opportunistic pathogens, were IgA-coated after the intervention. We suggest that the intestinal Ig response after vancomycin treatment prevents the intrusion of pathogens and bacterial components into systemic sites.